2005
DOI: 10.1530/rep.1.00426
|View full text |Cite
|
Sign up to set email alerts
|

Small heat shock protein 27 (Hsp27) expression is highly induced in rat myometrium during late pregnancy and labour

Abstract: The underlying mechanisms that regulate uterine contractions during labour are still poorly understood. A candidate regulatory protein is heat shock protein 27 (Hsp27). It belongs to the small heat shock protein family and can regulate actin cytoskeleton dynamics, act as a chaperone, and may regulate contractile protein activation. As a result, we hypothesized that Hsp27 expression would be highly induced during late pregnancy and labour. Hsp27 mRNA expression was significantly elevated (P < 0.05) on days 17 t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
24
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(28 citation statements)
references
References 48 publications
4
24
0
Order By: Relevance
“…AlphaB-crystallin expression has also been demonstrated to varying extent in numerous epithelial tumors (Pinder et al 1994). Similarly, Hsp27-1 expression was found in various benign and malignant tissues, eg, in retinal neurons (Whitlock et al 2005a(Whitlock et al , 2005b, in reproductive tissues (White et al 2005), in normal and neoplastic renal tissue (Neuhofer et al 2005;Tremolada et al 2005), and in malignant thyroid tissue (Akslen and Varhaug 1995).…”
Section: Introductionmentioning
confidence: 97%
“…AlphaB-crystallin expression has also been demonstrated to varying extent in numerous epithelial tumors (Pinder et al 1994). Similarly, Hsp27-1 expression was found in various benign and malignant tissues, eg, in retinal neurons (Whitlock et al 2005a(Whitlock et al , 2005b, in reproductive tissues (White et al 2005), in normal and neoplastic renal tissue (Neuhofer et al 2005;Tremolada et al 2005), and in malignant thyroid tissue (Akslen and Varhaug 1995).…”
Section: Introductionmentioning
confidence: 97%
“…We previously reported that HspB1 gene expression is highly upregulated in the rat myometrium during late pregnancy and labor (49); this finding parallels the increase in mechanical stress or distension exerted on the myometrium due to growing fetuses. It was also reported that, during late pregnancy, Ser 15 -phosphorylated HspB1 (pSer 15 HspB1) had a predominantly membrane-associated localization in situ within cells of the circular and longitudinal muscle layers.…”
mentioning
confidence: 59%
“…Uterine horn samples to be used for immunocytochemical analysis were fixed in 4% paraformaldehyde in 1ϫ PBS overnight with agitation and then washed in 1ϫ PBS for 24 h. Tissue samples were subjected to a graded ethanol series and xylene penetration and then embedded in paraffin wax. In other cases, excised uterine tissue was placed in ice-cold PBS (pH 7.4) and opened longitudinally for collection of the myometrium, as previously described (49). The endometrial layer was removed from all samples by gentle scraping with a scalpel blade prior to flash-freezing in liquid nitrogen and storage at Ϫ80°C.…”
Section: Animals and Tissue Collectionmentioning
confidence: 99%
See 1 more Smart Citation
“…HSP27 has also been shown to be S-nitrosylated under various conditions, leading to the possibility that regulation of HSP27 could be dependent on its nitrosylated state (Shi et al, 2008). HSP27 has also been shown to be highly induced in the myometrium during pregnancy and labor (White et al, 2005). Therefore, we consider HSP27 to be a prime candidate for future studies regarding the possible role of S-nitrosylation as a regulatory mechanism for HSP27 action.…”
Section: Discussionmentioning
confidence: 99%